2018
DOI: 10.18805/ag.r-116
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of root-knot nematode (Meloidogyne javanica (Treub) Chitwood) resistance in the Zimbabwean elite Virginia tobacco (Nicotiana tabacum L.) germplasm: A review

Abstract: Virginia tobacco (Nicotiana tabacum L.) is currently the most popular field cash crop grown in Zimbabwe. The farming of Virginia tobacco in Zimbabwe started during the late 19 th Century with introduced varieties which succumbed to most of the locally occurring pests and diseases. One major pest of tobacco that threatens the success of growing the crop has been the root-knot nematode [Meloidogyne javanica (Treub) Chitwood]. The pest attacks the root system of the crop from as early as the seedbed stage to such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
1
0
0
Order By: Relevance
“…Our report about RKNs corroborated the results of previous works with tobacco in Brazil (Araújo Filho et al., 2016) and elsewhere (Shava et al., 2018; Zeng et al., 2018). Other studies conducted in the same state reported the prevalence of M. javanica and M. arenaria on other economically important crops, like soybean (Kirsch et al., 2016; Márquez et al., 2021), kiwi (Somavilla et al., 2011), and potato (Medina et al., 2017).…”
Section: Discussionsupporting
confidence: 92%
“…Our report about RKNs corroborated the results of previous works with tobacco in Brazil (Araújo Filho et al., 2016) and elsewhere (Shava et al., 2018; Zeng et al., 2018). Other studies conducted in the same state reported the prevalence of M. javanica and M. arenaria on other economically important crops, like soybean (Kirsch et al., 2016; Márquez et al., 2021), kiwi (Somavilla et al., 2011), and potato (Medina et al., 2017).…”
Section: Discussionsupporting
confidence: 92%